Interactive Air Traffic Control automation in oceanic airspace - Freitas, Francisco (2014)
Air traffic controllers workload limits impose upper bounds to the amount of traffic manageable in a given air sector for a given time frame. Air Traf- fic Control (ATC) automation methods open the possibility of reducing this workload by shifting to the machine the tasks of (1) detecting poten- tial conflicts, and of (2) proposing to the controller ATC instructions that prevent such conflicts. We propose a decision support system based on a combinatorial optimization approach using a branch-and-bound method. Given a known traffic situation, we proceed by simulating the trajecto- ries of traffic, taking into account possible instructions to separate traffic. In this study we considered only flight level change instructions, given at report fixes. The cost function employed includes both a measure of vertical deviation from the filed flight plan (FPL) and the total amount of ATC instructions. The multi-criteria problem is solved interactively, as the operator directs the algorithm towards the solution, indicating its preferences at intermediate points in the simulation. As a case study, we analyse the problem of oceanic airspace, where conventional ATC is used due to the lack of radar coverage.